Principles of Islamic Civilization - Abd Rahman, Saodah binti (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Humans are created by God with minds that enable them to understand the role of life and to create a civilization. That is why people have history, and civilization is created from to generation to generation. Therefore, history and human civilization never end. When a nation falls, another nation exists. A government exists and collapses, but a civilization remains, because when a government falls, another government exists with a civilization that has its own unique history and civilization. Three thousand years ago, Rome was one of the largest empires in the world, and had a very old civilization. But today, Rome is a small city in Europe. Five hundred years ago, America was an isolated continent. But now, it is one of the countries that have world power and great civilization. It dominates the world politics and economy, and many third world countries. Its military power causes third world countries to submit to its orders. There are approximately twelve major civilizations in the world. Seven out of the twelve civilizations no longer exist. Those civilization are Mesopotamia, Egyptian, Cretan, Classical, Byzantine, Middle American and Andean. The other five surviving civilizations are China, Japan, India, Islam, and the West. But many scholars confirmed that the Russian Orthodox civilization is also among the large civilizations.